Impacts of armed conflicts on tuberculosis burden and treatment outcomes: a systematic review - Kefyalew Addis Alene; Temesgen Yihunie Akalu; Haileab Fekadu Wolde; Archie C A Clements; Eyob Alemayehu Gebreyohannes (BMJ Open)
Objectives This systematic review aimed to summarise existing literature on the impacts of armed conflicts on tuberculosis burden and treatment outcomes.Design A systematic review following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines.Data sources PubMed, Web of Science, Cumulative Index to Nursing and Allied Health Literature Plus, Scopus, ScienceDirect, Embase and medRxiv.Data extraction and synthesis Three reviewers independently screened, selected eligible studies and extracted data. A narrative review was undertaken to summarise the findings qualitatively.Results Eleven studies were included in this review, reporting on tuberculosis incidence rates, prevalence and treatment outcomes, including mortality. Overall, the impact of armed conflicts on case notifications was variable. Six studies reported overall increases in tuberculosis case notifications following the onset of conflicts, while three studies reported overall decreases in tuberculosis case notifications. Factors, including limited access to healthcare services, challenges in surveillance and laboratory confirmation, the destruction of health systems and incapacitating the healthcare workforce, contributed to a decrease in the number of notified cases. The higher tuberculosis notification in some of the studies could be attributed to the disruption of tuberculosis prevention and control programmes as well as increased socioeconomic deprivation, including malnutrition, mass migration, poor living conditions and overcrowding that are worsened during conflicts. Armed conflicts without effective interventions were associated with worse tuberculosis treatment outcomes, including lower proportions of people with treatment success and higher proportions of people with loss to follow-up, mortality and treatment failure. However, implementing various interventions in conflict settings (such as establishing a National Tuberculosis Control Programme) led to higher tuberculosis notification rates and treatment success.Conclusion The impact of armed conflicts on tuberculosis notification is complex and is influenced by multiple factors. The findings of this review underscore the importance of concerted efforts to control tuberculosis in conflict settings using available resources.